Spatial and Temporal Distribution of Cassava Green Mite, Mononychellus tanajoa Bonder (Acarina: Tetranychidae) in Tanzania - , B. S. Wudil; , G. M. Rwegasira; , A. B. Kudra; , S. Jeremiah (Archives of Current Research International, 2017)
Two diagnostic surveys were conducted during the 2015 and 2016 growing seasons in three major cassava growing zones of Tanzania. The studies aimed at establishing the spatial and temporal distribution of M. tanajoa on commonly grown commercial cassava varieties landraces in Tanzania. A total of 2,700 plants in 90 fields were assessed in nine districts of which five fields were in the Lake zone and two districts in each of the Southern and Eastern zones. Results indicated that the distribution of M. tanajoa significantly (P = .05) differed across seasons, Southern and Lake zones were statistically similar and higher in M. tanajoapopulation than the Eastern zone. Crop age, altitude and cassava varieties significantly (P = .05) influenced the population of M. tanajoa while crop mixture (inter cropping) had no significant effect in both seasons. The relationship among the environmental variables and population distribution of M. tanajoa were significant (P = .05). Variations in M. tanajoa population within and between seasons and locations were due to differences in the cassava varieties and the environment. The survival, perpetuation and distribution of M. tanajoa were attributed to the crop age, suitability of the variety and intensity of cassava cultivation.